2006
DOI: 10.1158/0008-5472.can-05-3582
|View full text |Cite
|
Sign up to set email alerts
|

HSulf-1 Inhibits Angiogenesis and Tumorigenesis In vivo

Abstract: We previously identified HSulf-1 as a down-regulated gene in several tumor types including ovarian, breast, and hepatocellular carcinomas. Loss of HSulf-1, which selectively removes 6-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
143
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(164 citation statements)
references
References 37 publications
11
143
3
Order By: Relevance
“…Forty-fold higher expression of heparan sulfate 6-O-endosulfatase1 (Sulf1) was noted in blood vessels from wound-site compared with that from intact skin. Sulf1 has been recently recognized to be anti-angiogenic (9). The ␣-1 chain of collagen IV (also known as arresten) or COL4A1 was overexpressed in blood vessels of wound site by 37-fold compared with that in vessels from intact skin.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-fold higher expression of heparan sulfate 6-O-endosulfatase1 (Sulf1) was noted in blood vessels from wound-site compared with that from intact skin. Sulf1 has been recently recognized to be anti-angiogenic (9). The ␣-1 chain of collagen IV (also known as arresten) or COL4A1 was overexpressed in blood vessels of wound site by 37-fold compared with that in vessels from intact skin.…”
Section: Resultsmentioning
confidence: 99%
“…In this report we demonstrated that DNA methylation and histone modifications regulate HSulf-1 expression and Epigenetic silencing of HSulf-1 J Staub et al provided the first evidence of methylation in combination with chromatin histone modification as a mechanism of HSulf-1 inactivation in ovarian cancer. Re-expression of HSulf-1 has been shown to inhibit tumor growth (Dai et al, 2005;Lai et al, 2006;Narita et al, 2006). In this study, we analysed the relationship between HSulf-1 induction with 5-aza-dC and chemoresponse of ovarian cancer cell lines in vitro and correlated HSulf-1 expression in patient samples to a better therapeutic index.…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrate that HSulf-1 expression is correlated with response to chemotherapy and thus may be useful in conjunction with other molecular markers, in predicting chemosensitivity. Given the observation that the presence of HSulf-1 also inhibits angiogenesis in vivo (Narita et al, 2006), a combination therapy that includes demethylating agents and or HDACs inhibitors with classical antineoplastic drugs such as carboplatin or taxol or antiangiogenic drug may benefit patients with tumors that lack HSulf-1 expression by promoting the expression of epigenetically controlled genes such as HSulf-1 involved in inhibiting growth and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, therefore, that tumour growth in cancer cells overexpressing SULF2 is potentiated by tumour angiogenesis. In hepatocellular and breast carcinomas, however, overexpression of SULF1 inhibits tumour growth/angiogenesis partially by inhibiting FGF, HGF, and VEGF stimulation of tumour cell growth and metastasis (Lai et al, 2004b(Lai et al, , 2008 and correlates with the low levels of FGF/HS/FGFR2 signal complexes formed in SULF1-expressing cells in vitro (Lai et al, 2006;Narita et al, 2006). Clearly, in pathological conditions sulfatases can have both proand anti-angiogenic roles depending on the context of the perturbed signalling environment.…”
Section: Introductionmentioning
confidence: 99%